International Competitiveness, Job Creation and Job Destruction - An Establishment-level Study of German Job Flows - Moser, Christoph; Urban, Dieter; Weder di Mauro, Beatrice (Journal of International Economics, 2010)
This study investigates the impact of international competitiveness on net employment, job creation, job destruction, and gross job flows for a representative sample of German establishments from 1993 to 2005. We find a statistically significant but economically small effect of real exchange rate shocks on employment, comparable to the one found in studies for the United States. However, contrary to the United States, the employment adjustment (among surviving firms) operates mainly through the job creation rather than the job destruction rate. Job destruction occurs essentially through discrete events such as restructuring, outsourcing and bankruptcy. We suggest that these findings are consistent with a highly regulated labor market, in which smooth adjustment is costly and possibly delaye